Enzyme production by solid-state fermentation: Application to animal nutrition - Graminha, E. B. N. [UNESP]; Gongalves, A. Z. L. [UNESP]; Pirota, R. D. P. B. [UNESP]; Balsalobre, M. A. A.; Da Silva, R. [UNESP]; Gomes, E. [UNESP] (Elsevier B.V., 2008)
Many microorganisms that decompose lignocellulosic material are being studied as producers of enzymes to perform enzymatic hydrolysis of the lignocellulosic material present in residues from the agroindustries. Although the cellulose and hemicellulose present in these materials have their value for feeding cattle, their bioavailability requires breakdown of the bonds with indigestible lignin. Predigestion of such materials with ligninases, xylanases and pectinases (cellulase free) may transform the lignocellulosic substrate into a feed with greater digestibility and higher quality for ruminants.. This review provides an overview of variables to be considered in the utilization of fungal plantdepolymerizing enzymes produced by solid-state fermentation from agricultural production residues in Brazil. (c) 2007 Elsevier B. V. All rights reserved.
Keywords: animal nutrition; by-products; Enzyme; Solid state fermentation (SSF); Thermophilic fungi